2014
DOI: 10.3109/10717544.2014.913323
|View full text |Cite
|
Sign up to set email alerts
|

High drug load, stable, manufacturable and bioavailable fenofibrate formulations in mesoporous silica: a comparison of spray drying versus solvent impregnation methods

Abstract: Encapsulation of drugs in mesoporous silica using co-spray drying process has been recently explored as potential industrial method. However, the impact of spray drying on manufacturability, physiochemical stability and bioavailability in relation to conventional drug load processes are yet to be fully investigated. Using a 2(3) factorial design, this study aims to investigate the effect of drug-loading process (co-spray drying and solvent impregnation), mesoporous silica pore size (SBA-15, 6.5 nm and MCM-41, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…Many of these new chemical entities (NCEs) failed to be used in clinical therapy as they have poor bioavailability due to their limited solubility or slow dissolution rate in the gastrointestinal tract (Hong et al, 2014). Converting crystalline drugs into their amorphous counterparts is an efficient way to improve the dissolution rate and solubility of poorly water-soluble drugs, especially for biopharmaceutics classification system (BCS) Class II compounds (Srinarong, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these new chemical entities (NCEs) failed to be used in clinical therapy as they have poor bioavailability due to their limited solubility or slow dissolution rate in the gastrointestinal tract (Hong et al, 2014). Converting crystalline drugs into their amorphous counterparts is an efficient way to improve the dissolution rate and solubility of poorly water-soluble drugs, especially for biopharmaceutics classification system (BCS) Class II compounds (Srinarong, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…With a Tg of 70.5 C, Soluplus had a wide extrusion temperature range (Zhang, 2013). Also its high flow-ability and excellent extrudability made it suitable for the extrusion process (Hong et al, 2014). Numerous studies based on Soluplus have shown that it can enhance the dissolution rates of poorly soluble drugs.…”
Section: Introductionmentioning
confidence: 99%
“…This approach involves dispersing the carrier in a solution of the drug in a volatile solvent followed by spray drying of the dispersion. Compared to solvent based techniques, this method produces more stable amorphous state of the drug with considerably enhanced dissolution rate and oral bioavailability (182,183).…”
Section: Drug Loading Methods For Mesoporous Materialsmentioning
confidence: 99%
“…In addition these conventional methods have intrinsic disadvantages such as the use of organic solvents that will require a subsequent solvent elimination process; impacting on time and cost factors (129). Therefore, supplementary approaches have been proposed to load drug into mesoporous carriers without affecting active stability such as supercritical fluids method (129,181), co-spray drying (182,183) and microwave irradiation (184). The supercritical fluid method (e.g.…”
Section: Drug Loading Methods For Mesoporous Materialsmentioning
confidence: 99%
“…[12][13][14] In cellular systems, low toxicity and high uptake of MSNs have been well established in studies stemming from the past decade. 15 The ordered pore structure accompanied with the consequential high surface area and pore volume provides the nanocarriers with a high loading capacity 16 and offers efficient protection for the oligonucleotide cargo before reaching the point of release. 17,18 Furthermore, MSNs may facilitate slow, sustained and controlled release 19 owing to their design flexibility that enables multifunctionality as well as allows for sequential release.…”
Section: Introductionmentioning
confidence: 99%